Quantum measurements on finite dimensional systems: relabeling and mixing - Haapasalo E; Heinosaari T; Pellonpaa JP (SPRINGER, 2025)
Quantum measurements are mathematically described by positive operator valued measures (POVMs). Concentrating on finite dimensional systems, we show that one can limit to extremal rank-1 POVMs if two simple procedures of mixing and relabeling are permitted. We demonstrate that any finite outcome POVM can be obtained from extremal rank-1 POVMs with these two procedures. In particular, extremal POVMs with higher rank are just relabelings of extremal rank-1 POVMs and their structure is therefore clarified.